INTERPRETASI EKOWISATA OLEH PEMANDU WISATA PADA DAYA TARIK WISATA LUMBA-LUMBA DI BALI: INTERPRETATION OF ECOTOURISM BY TOUR GUIDES AT THE DOLPHIN TOURIST ATTRACTION IN BALI - Nathalia Sihombing; Dalem, A.A. Gde Raka; Astarini, Ida Ayu (Program Studi Biologi Universitas Udayana, 2025)
Dolphin ecotourism is a tourism activity that is educational and related to tour guides who provide interpretation, so this research is important for the sustainability of better dolphin ecotourism. This research was conducted from November to December 2025 which aims to determine the type of interpretation, means of interpretation and the quality of interpretation provided to tourists. The data collection method is accidental sampling by conducting interviews, direct observation, distributing questionnaires and examining related documents. The guides interviewed were 15 people and 25 tourists. The results obtained in this study indicate that the type of interpretation used by dolphin tour guides in Bali amounted to seven types of interpretation types, namely, guided tour, point duty, roving interpretation, lecture or talk, demonstration, translator and living history. The means of interpretation used amounted to four types of facilities, namely print (100%), self-guiding signs (100%), cell phones or social media (100%) and interpretation boards (100%). The overall quality of tour guide interpretation is assessed based on aspects of knowledge, skills and attitude. The quality of the guide's interpretation received an average score that was classified in the good category with a presentation of 76.6%, from the knowledge of 81.2%, the skill of 99.5% and the attitude of 75%. The superior aspect is in the skill aspect of 99.5%. This value indicates that the quality of interpretation of dolphin tour guides in Bali is said to be good.